Speech perception in the first year of life (2014)
Language acquisition involves a number of complex skills that evolve in correlation with each other, thus making it possible for learners of their frst spoken language —or sign language— to achieve the best results with minimal effort, as long as they do so within the appropriate period of time. In this regard, it is proposed that early speech perception has a primary role in language acquisition. In order to provide an overview of the current scientifc knowledge as to the capabilities of children under the age of one to perceive spoken language, this paper presents the results of the most relevant research on discrimination of classes and types of words, interidiomatic and prosodic discrimination, phonological and phonotactic discrimination, as well as recognition of distributional regularities amongst the elements of the speech signal. © 2012, Konrad Lorenz University Foundation.